A NOS1 variant implicated in cognitive performance influences evoked neural responses during a hight density EEG study of early visual perception. - GILL, MICHAEL; CORVIN, AIDEN; MORRIS, DEREK; DONOHOE, GARY; FAHEY, CIARA (Wiley Open Access, 2012)
Background: The nitric oxide synthasase‐1 gene (NOS1) has been implicated in mental disorders including schizophrenia and variation in cognition. The NOS1 variant rs6490121 identified in a genome wide association study of schizophrenia has recently been associated with variation in general intelligence and working memory in both patients and healthy participants. Whether this variant is also associated with variation in early sensory processing remains unclear. Methods: We investigated differences in the P1 visual evoked potential in a high density EEG study of 54 healthy participants. Given both NOS1's association with cognition and recent evidence that cognitive performance and P1 response are correlated, we investigated whether NOS1's effect on P1 response was independent of its effects on cognition using CANTAB's spatial working memory (SWM) task. Results: We found that carriers of the previously identified risk “G” allele showed significantly lower P1 responses than non‐carriers. We also found that while P1 response and SWM performance were correlated, NOS1 continued to explain a significant proportion of variation in P1 response even when its effects on cognition were accounted for. Conclusion: The schizophrenia implicated NOS1 variants rs6490121 influences visual sensory processing as measured by the P1 response, either as part of the gene's pleiotropic effects on multiple aspects of brain function, or because of a primary influence on sensory processing that mediates the effects already seen in higher cognitive processes.
Keywords: Visual evoked potentials; Working memory; NOS1 gene; Schizophrenia; Genes & Society; Neuroscience